A Single Dose SARS-CoV-2 Replicon RNA Vaccine Induces Cellular and Humoral Immune Responses in Simian Immunodeficiency Virus Infected and Uninfected Pigtail Macaques - O’Connor, Megan A.; Erasmus, Jesse H.; Randall, Samantha; Archer, Jacob; Lewis, Thomas B.; Brown, Brieann; Fredericks, Megan; Groenier, Skyler; Iwayama, Naoto; Ahrens, Chul; Garrison, William; Wangari, Solomon; et al. (Frontiers in Immunology, 2021)
The ongoing COVID-19 vaccine rollout is critical for reducing SARS-CoV-2 infections, hospitalizations, and deaths worldwide. Unfortunately, massive disparities exist in getting vaccines to vulnerable populations, including people living with HIV. Preliminary studies indicate that COVID-19 mRNA vaccines are safe and immunogenic in people living with HIV that are virally suppressed with potent antiretroviral therapy but may be less efficacious in immunocompromised individuals. This raises the concern that COVID-19 vaccines may be less effective in resource poor settings with limited access to antiretroviral therapy. Here, we evaluated the immunogenicity of a single dose COVID-19 replicon RNA vaccine expressing Spike protein (A.1) from SARS-CoV-2 (repRNA-CoV2S) in immunocompromised, SIV infected and immune competent, naïve pigtail macaques. Moderate vaccine-specific cellular Th1 T-cell responses and binding and neutralizing antibodies were induced by repRNA-CoV2S in SIV infected animals and naïve animals. Furthermore, vaccine immunogenicity was elicited even among the animals with the highest SIV viral burden or lowest peripheral CD4 counts prior to immunization. This study provides evidence that a SARS-CoV-2 repRNA vaccine could be employed to induce strong immunity against COVID-19 in HIV infected and other immunocompromised individuals.